Building Child-Friendly Schools in Rural Areas: The Power of Inclusive Education Management - M. Holili, M; Syarif, Zainuddin; Masrurah, Waqiatul; Ravasdeh, Ziyad (JURNAL AL-TANZIM, 2025)
This study aims to analyse education empowerment in rural areas through inclusive management to create child-friendly schools. The study is based on the increasing need for an education system that can serve all children, including those with special needs, especially in rural areas, so inclusive management in schools plays a vital role in ensuring equal opportunities for all students. This study uses a qualitative approach with a case study methodology, using in-depth interviews and observations as data collection techniques, with data analysis according to the Miles and Huberman approach. The study's findings revealed that empowering child-friendly schools in rural areas requires the implementation of a responsive curriculum, a safe and inclusive school environment, qualified teachers with continuous professional development, and active community participation. A secure and discrimination-free environment fosters students' social and emotional development, while professional development for teachers enhances their ability to meet the various needs of students. In addition, community participation in inclusive management strengthens the support of resources, facilities, and social collaboration, significantly contributing to the creation of stronger inclusive education in rural areas. The study contributes to understanding the essential components needed to implement inclusive education in rural areas.